Antiretroviral Therapy and Detection of High-grade Cervical Intraepithelial Neoplasia (CIN2+) at Post-CIN Management Follow-up Among Women Living With Human Immunodeficiency Virus: A Systematic Review and Meta-Analysis. (11th March 2020) - Atemnkeng, Njika; Aji, Abang Desmond; de Sanjose, Silvia; Mayaud, Philippe; Kelly, Helen
Abstract: Background: We evaluated the association of antiretroviral therapy (ART), CD4+ count and human immunodeficiency virus (HIV) plasma viral load (PVL) on high-grade cervical intraepithelial neoplasia (CIN2+) detection at follow-up after CIN management among women living with HIV (WLHIV). Methods: Medline, Embase, Global Health, and PubMed were searched from 1 January 1996 to 15 January 2020. Eligible studies investigated the association of ART, CD4+ count, or HIV PVL on histology-confirmed CIN2+ detection at follow-up. Summary estimates were obtained using random-effects meta-analyses; heterogeneity was examined using I 2 statistic. PROSPERO registration: CRD42018115631. Results: Eight studies representing 9 populations were identified, including 1452 WLHIV followed between 6 and 33 months post-CIN management. Pooled data from 8 populations (n = 1408) suggested weak evidence of a decreased risk of CIN2+ detection at follow-up among ART users compared to ART-naive women (crude odds ratio [cOR] = 0.70, 95% confidence interval [CI]: .36–1.36; I 2 = 64.5%, P  = .006; adjusted risk ratio [aRR] from 3 studies = 0.66, 95% CI: .20–2.24; I 2 = 78.7%, P  = .009). A significant association was observed in high-income countries (cOR = 0.24, 95% CI: .13–.45; I 2 = 0.0%, P  = .77) but not in low and middle-income countries (cOR = 1.13, 95% CI: .67–1.92; I 2 = 18.8%, P  = .30). In 3 populations, ART users with HIV PVL <50 copies/ml were less likely to have CIN2+ detection at follow-up (vs ≥50 copies/mL: cOR = 0.55, 95% CI: .32–.94; I 2 = 0.0%, P  = .23). There was weak evidence of decreased CIN2+ detection at follow-up among WLHIV with higher contemporary CD4+ cell counts (≥200 cells/µL vs <200 cells/µL [cOR = 0.36, 95% CI: .04–3.13; I 2 = 81.3%, P  = .021]) and significant evidence among women with a higher nadir CD4+ count (≥350 cells/µl vs <200 cells/µl [adjusted hazard ratio [aHR] = 0.35, 95% CI: .15–.84; I 2 = 0%, P  = .64]). Conclusion: ART may reduce the risk of CIN2+ detection at follow-up; this effect is most likely enhanced by a combination of adequate HIV control and excisional CIN treatment. Our findings support recommendations of early ART and the integration of CIN2+ screening and management into HIV care. Abstract : We evaluated the association of antiretroviral therapy (ART) on cervical intraepithelial neoplasia (CIN2+) detection at follow-up among women living with human immunodeficiency virus (HIV) and found that ART was associated with a decreased risk of CIN2+ detection at follow-up, particularly in high-income countries and following excisional CIN management.